(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Burn wound infections significantly increase morbidity, length of hospital stay, and mortality. Bangladesh carries a disproportionately high burden due to limited burn care facilities and rising antimicrobial resistance (AMR). Objective: To identify the bacteriological profile and antimicrobial susceptibility patterns among burn wound infections in a tertiary care hospital in Bangladesh. Methods: This retrospective cross-sectional study included 104 burn patients from January 2023 to December 2023 in the Burn and Plastic Surgery Department at Comilla Medical College Hospital. Wound swabs were cultured using standard microbiological techniques, and antimicrobial susceptibility testing was performed according to CLSI guidelines. Results: Among 104 samples, 96.16% yielded microbial growth. Pseudomonas spp. was the predominant isolate (43.04%), followed by Staphylococcus aureus (19.62%) and Klebsiella spp. (10.76%), E. coli (8.86%), Proteus spp. (6.96%), Acinetobacter spp. (6.33%), and Candida spp. (4.43%). Colistin exhibited the highest activity against Gram-negative bacteria, while Methicillin Resistant Staphylococcus Aureus (MRSA) and Methicillin Sensitive Staphylococcus Aureus (MSSA) showed 100% susceptibility to vancomycin and linezolid. Conclusion: Gram-negative bacteria dominate burn wound infections in Bangladesh, with total body surface area (TBSA), flame burns, and inhalation injury significantly increasing the risk of resistance. Targeted infection control, early microbiological surveillance, and antibiotic stewardship are critical to reducing the burden of resistant organisms and improving clinical outcomes J Com Med Col Teachers’ Asso Jan 2026; 30(1): 25-30